Diffractive elements in thermal imaging monofocal dual-band objectives: design and technological aspects - G.I. Greisukh; I.A. Levin; O.A. Zakharov (Компьютерная оптика)
Using the example of the development of two simple dual-band monofocal IR objectives, approaches to the layout and design of their optical schemes are demonstrated, depending on whether compensation for the effects of temperature changes on the optical characteristics of these lenses is required or not. It is shown that in the case when thermal compensation is not required, superior optical characteristics can be achieved in a simple triplet, in which the flat surface of the frontal fractional lens carries a diffractive microstructure. In the case of passive athermalization, the optical scheme of the objective becomes more complicated and consists of refractive two-line power and correction components, in the latter of which the flat surface of one of the lenses carries a diffractive microstructure. Due to highly efficient diffractive microstructures, the longitudinal chromaticism of both objectives is reduced almost to the diffraction limit and, in combination with a low level of residual monochromatic aberrations at high light intensity, the maximum resolution is provided for uncooled microbolometers used as matrix receivers.